2021
DOI: 10.1080/08941920.2021.2011514
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Science and Discursive Violence: A Response to Two Rejoinders

Abstract: We respond to two rejoinders to our review article "Science for Success," which proposed fuller contextualization of epistemological approach, researcher position and interests in conservation research. This way readers-including reviewers and journal editors-can better understand and interpret findings. We suggest this contextualization is particularly important when conservation and development professionals undertake research about programs they are involved in, as this can potentially create a conflict of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…More examples can be mentioned, but the point is that in both historical and current south(ern) African conservation there seems to be a structural tendency to marketize success and achievements and to minimize or even ignore contradictions, failures and the continuing socio-environmental injustices underpinning all of it (Büscher, 2014). This includes conservation researchers working with or for large conservation NGOs, some of whom even actively try to silence opinions and ideas that do not suit their agendas (Koot et al, 2023a; Koot et al, 2023b).…”
Section: Southern African Conservation In the Worldmentioning
confidence: 99%
“…More examples can be mentioned, but the point is that in both historical and current south(ern) African conservation there seems to be a structural tendency to marketize success and achievements and to minimize or even ignore contradictions, failures and the continuing socio-environmental injustices underpinning all of it (Büscher, 2014). This includes conservation researchers working with or for large conservation NGOs, some of whom even actively try to silence opinions and ideas that do not suit their agendas (Koot et al, 2023a; Koot et al, 2023b).…”
Section: Southern African Conservation In the Worldmentioning
confidence: 99%
“…The trophy hunting debate is vulnerable to polarization, particularly since morality plays a significant role in the discourse (Fischer et al, 2013; Vucetich et al, 2019; see also Bloom, 2013; Garrett & Bankert, 2020). Morally charged debates can cultivate biases, increase tensions (for instance, see Koot et al, 2020, 2022 and comments on it; Dickman et al, 2021; Naidoo et al, 2021) and undermine collaborative effort within the conservation community. Furthermore, research has shown that people whose attitudes are anchored in moral principles perceive their positions as universally applicable and objectively true (Schwalbe et al, 2020; Skitka, 2014).…”
Section: Introductionmentioning
confidence: 99%